Correction: Yaseen et al. Photo-Assisted Removal of Rhodamine B and Nile Blue Dyes from Water Using CuO–SiO2 Composite. Molecules 2022, 27, 5343 - Muhammad Yaseen; Muhammad Humayun; Abbas Khan; Muhammad Idrees; Nasrullah Shah; Shaista Bibi (Molecules)
Citation of the publication (our own previous work), Yaseen, M [...]